Prevalence of early childhood caries among 3-5 year old pre-schoolers in schools of Marathahalli, Bangalore - Shilpi Singh; N Vijayakumar; H R Priyadarshini; M Shobha (Wolters Kluwer Medknow Publications, 2012)
Background: Dental caries among preschool children is still a major public health problem in many developing countries including India. Hence the aim of the present study was to find out the prevalence of Early Childhood Caries among 3-5 year old pre-schoolers in schools of Marathahalli, Bangalore. Materials and Methods: A cross sectional study was conducted on 717 pre-schoolers in 6 schools of Marathahalli. Clinical examination was performed and deft index was recorded using Gruebell's criteria. Early Childhood Caries was diagnosed using Early Childhood Caries Diagnostic Criteria, consistent with the NIDCR workshop statement. Data was analysed using SPSS 15.0 and descriptive statistics was applied. Chi-square test was used to find out the significant differences. The level of significance was taken at P value < 0.05. Results: Prevalence of early childhood caries was 40% with a mean deft of 1.89 (+3.3) and Significant Caries Index score was 5.51. 44.8% of 3 year old had Early Childhood Caries, 35% of 4 year old children and 41% of 5 year old had Early Childhood Caries. Almost, all of deft was due to untreated caries. Conclusion: The results of the present study calls for a need to focus on pre-schoolers' oral health and parental education for prevention and early detection of Early Childhood Caries. A high Significant Caries Index in this study population indicates a more targeted approach for high risk pre-schoolers.